(untitled) (Journal of the College of Education for Women, 2023)
Language always conveys ideologies that represent an essential aspect of the world we live in. The beliefs and opinions of an individual or community can be organized, interacted with, and negotiated via the use of language. Recent researches have paid attention to bullying as a social issue. They have focused on the psychological aspect of bullying rather than the linguistic one. To bridge this gap, the current study is intended to investigate the ideology of bullying from a critical stylistic perspective. The researchers adopt Jeffries’ (2010) critical stylistics model to analyze the data which is five extracts taken from Hunt’s Fish in a Tree (2015). The analysis demonstrates that the critical stylistic tools contribute significantly to the linguistic formulation of the concept of bullying and account for a significant amount of the meaning of the text under consideration. The study concludes that the ideology of bullying is represented through using most of the stylistic tools but with different bullying acts.